2005
DOI: 10.1097/01.aids.0000183625.97170.59
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of nevirapine in HIV-infected children receiving an adult fixed-dose combination of stavudine, lamivudine and nevirapine

Abstract: The administration of GPO-VIR S30 fixed-dose combination tablets in fractions or as a whole tablet to children resulted in appropriate NVP exposure and satisfactory virological and immunological benefit. This finding confirms the effectiveness of using a fixed-dose combination as a "transitional option" while waiting for a paediatric fixed-dose combination drug formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…In a Thai study [18], only 3% of children (one of 34) who received divided adult FDCs (GPO-VIR S30; GPO, Thailand; equivalent to Triomune 30) had subtherapeutic nevirapine concentrations (defined as < 3.4 mg/l) and the average nevirapine dose was considerably higher at 328 mg/m 2 [18] compared with 265 mg/m 2 in our previous study [3]. The average age was, however, higher and none were less than 3 years (compared with 13% in our previous study), nor did any receive quarter or threequarter tablets (compared with 42%) [3].…”
Section: Discussionmentioning
confidence: 99%
“…In a Thai study [18], only 3% of children (one of 34) who received divided adult FDCs (GPO-VIR S30; GPO, Thailand; equivalent to Triomune 30) had subtherapeutic nevirapine concentrations (defined as < 3.4 mg/l) and the average nevirapine dose was considerably higher at 328 mg/m 2 [18] compared with 265 mg/m 2 in our previous study [3]. The average age was, however, higher and none were less than 3 years (compared with 13% in our previous study), nor did any receive quarter or threequarter tablets (compared with 42%) [3].…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11 The majority of patients in our cohort were treated with split adult FDC of 2 NRTIs and 1 NNRTI, confirming other findings that good outcomes can be achieved with this treatment strategy. 18,19 It should be noted, however, that this practice is a suboptimal interim strategy 13 pending prequalification of pediatric formulations of FDCs. The majority of the patients were in an advanced stage of HIV infection, similar to many settings where HIV/AIDS care for children has been commenced.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators concluded that dividing FDC Triomune should be used with caution to avoid inappropriate dosing and that further study is needed on the effects of malnutrition on NVP pharmacokinetics in children. However in Thailand, good virologic and immunologic response as well as appropriate NVP exposure has been reported among children treated with adult fixed dose combinations of stavudine, lamivudine, and nevirapine (GPO-VIR) 31 . In spite of the disadvantages of using adult FDC to treat children, our data show that children can be effectively treated with adult FDC up to 96 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%